2013 Pilot External Sector Report : Individual Economy Assessments. (Policy Papers; Policy Paper ;, 2013)
The external sector assessments use a wide range of methods, including the External Balance Assessment developed by the IMF's Research Department to estimate desired current account balances and real exchange rates (Boxes 6, 7 and Annex III of the Pilot Report describe the methodology and challenges). In all cases, the overall assessment is based on the judgment of IMF staff drawing on the inputs provided by these model estimates and other analysis and the estimates are subject to uncertainty. The assessments were initially based on the Spring 2013 WEO and an exchange rate reference period of the average of 2012. Potential policy responses are those which would work to reduce imbalances.